To Conform or To Perform? Mimetic Behaviour, Legitimacy‐Based Groups and Performance Consequences* - Barreto, Ilídio; Baden‐Fuller, Charles (Journal of Management Studies, 2006)
abstract The study of interorganizational imitation has been an important strand in the recent literature on institutional theory. This paper offers new insights for our understanding of mimetic isomorphism and its reliance on legitimacy: we suggest that legitimacy‐based reference groups guide firms in their mimetic behaviour, that firms undertake imitation even against their own ex ante information, and that legitimacy‐based imitation contributes negatively to firms' profitability. We examine Portuguese bank branching decisions between 1988 and 1996 and find that banks imitate their legitimacy‐based groups, and not only towards ex ante (firm‐specific) attractive locations, but also towards unattractive locations; we also find that mimetic branching produces a negative effect on profitability. We conclude that these results show the importance of legitimacy pressures on organization decisions and the tension between the pressure to conform and the pressure to perform.